DISCOURSE ISSUES IN ENGLISH LANGUAGE TEACHING - Nugraha, Indra (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
The relationship between linguistics and language education is particularly interesting to follow. In language education, especially English, linguistics provides information on language rules and structure knowledge. However, due to the notion that teaching English language must be taught in a multilingual environment and intercultural approach, linguistics must also provide a complete description of language. To describe language in use, discourse is the key. To linguistic students, discourse is a familiar term, while to some language education students, the term may be unfamiliar. This raises many issues, including what is discourse. Is it important to learn? Is it relatable to language education, particularly English? To answer these questions, we need to take a glimpse of discourse analysis.